Self-conception of Local Dangdut Female Singers - Nicko Besari, Adita; Naryoso, S.Sos, M.Si, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
The existence of local dangdut singers in family and environment tent to cause barriers in interpersonal communication which they have done. The prejudices and negative stereotypes are what the local dangdut singers’ get that can affect the forming process of the self-conception. These phenomena have affected the trusts and attitude of local dangdut singers when doing conflict resolution. This research uses phenomenology tradition approaches for learning from the local dangdut singers’ experience when the self-conception is in forming process in conflict resolution. It is alsouses the theory of perceptual accentuation that emphasizes the self-conception of local dangdut singer that affects the trust to handle the barriers. As the effort of doing the conflict resolution, this research also uses An Attribution Theory of Conflict, which emphasizes the efforts in achieving and conflict solving. The result of the research is shows that the relationships of local dangdut singers are tent to fail and could not find familiarity and even reach the destruction state. The prejudices and negative stereotype gives influence to local dangdut singers in personal. They value their self as a negative that affect their trust and the ability to handle the barriers. These things impacts on attitude variation when doing conflict resolution and gives more output variation of conflict solving in this research.